Analisis Semiotik Pesan Iklan @GojekIndonesia sebagai Media Informasi - Hubert Jan Muaya; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research aims to analyze the messages in Gojek advertisements as a medium of information using a semiotic approach based on Ferdinand de Saussure’s theory. Gojek advertisements were chosen as the subject of this study due to their success in capturing public attention and their significant role in conveying information to consumers. Saussure’s semiotic theory focuses on the concept of the sign, which consists of two main components: the signifier and the signified. This study seeks to identify how Gojek advertisements construct meaning through the relationship between the signifier and the signified within the conveyed message. By examining the visual and verbal content in Gojek ads, this research explores how symbolic elements—such as images, words, and contextual cues—interact to create meanings that are understood by the audience. The research method used is qualitative descriptive analysis, employing a literature review approach and data collection through documentation of Gojek advertisements circulated via digital media. The findings show that Gojek advertisements use a combination of visual elements—such as logos, colors, and images—and verbal elements—such as slogans and text messages—to communicate information about the convenience and speed of its services. Furthermore, these advertisements construct a meaning that associates Gojek with values such as innovation, efficiency, and affordability. Overall, this study concludes that through Saussure’s semiotic analysis, Gojek advertising can be understood as a complex sign system that functions to convey information while shaping social perceptions of the Gojek brand. Pendekatan semiotika Saussure menitikberatkan pada konsep tanda, yang terdiri dari dua unsur utama: penanda (signifier) dan petanda (signified). Penelitian ini bertujuan mengungkap bagaimana makna dalam iklan Gojek terbentuk melalui hubungan antara penanda dan petanda dalam pesan yang disampaikan. Dengan menganalisis elemen visual dan verbal dalam iklan Gojek, penelitian ini menunjukkan bagaimana unsur-unsur simbolik seperti gambar, kata-kata, dan konteks bekerja secara sinergis untuk membentuk makna yang dapat dipahami oleh audiens. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif, dengan teknik studi pustaka serta pengumpulan data berupa dokumentasi iklan Gojek yang disebarluaskan melalui media digital. Hasil penelitian menunjukkan bahwa iklan Gojek memadukan penanda visual seperti logo, warna, gambar, dan bahasa tubuh dengan penanda verbal seperti slogan dan teks untuk mengkomunikasikan kemudahan dan kecepatan layanan. Iklan-iklan tersebut juga membangun konotasi yang mengaitkan Gojek dengan nilai-nilai modernitas, efisiensi, dan keterjangkauan. Secara keseluruhan, penelitian ini menyimpulkan bahwa melalui analisis semiotika Saussurean, iklan Gojek dapat dipahami sebagai suatu sistem tanda yang kompleks, yang tidak hanya berfungsi menyampaikan informasi, tetapi juga membentuk persepsi sosial terhadap merek Gojek.